Precise dimensions : a history of units from 1791-2018 - Cooper, Malcolm (Malcolm J.); Grozier, Jim (IOP (Series). Release 4., 2017)
Units are the foundation for all measurement of the natural world, and from which standard, our understanding develops. This book, stemming from a conference on the history of units organised by the editors, provides a detailed and discursive examination of the history of units within physics, in advance of the proposed redefinition of the SI base units at the General Conference on Weights and Measures in 2018. It features contributions from leading researchers in metrology and history.